Persepsi Pengusaha Walet Terhadap Pembayaran Zakat Budidaya Sarang Burung Walet Di Kelurahan Benteng Provinsi Riau Di Tinjau Dari Konsep Ekonomi Islam - Awal Bahru; Rafidah; Neneng Sudharyati (CV. KAMPUS AKADEMIK PUBLISING, 2023)
In Benteng Village there is a swallow's nest cultivation business which has a fairly high income every time it is harvested. However, there are only a number of swallow nest entrepreneurs who carry out their obligations towards the business they are doing, namely issuing zakat, and there are also some entrepreneurs who issue zakat not in accordance with Islamic sharia provisions and Islamic economic concepts, and there are also some swallow nest entrepreneurs who does not issue zakat at all even though it has reached its nisab. In this regard, this study aims to find out and analyze how the perceptions of swallow entrepreneurs towards payment of zakat for swallow's nest cultivation in Benteng Village, then how are the perceptions of religious leaders in Benteng Village regarding zakat payments for swallow's nest cultivation and to find out the mechanism for implementing bird's nest zakat payments. swallow in the Benteng Village and in terms of Islamic economic concepts. The author in this study used a qualitative approach. The data sources used are primary data sources and secondary data sources. Data collection techniques used are observation, interviews, and documentation. The results of the research that has been carried out indicate that the perceptions of entrepreneurs regarding the payment of zakat for the cultivation of swallow's nests in the Benteng village are not fully aware of the concept and obligation to pay zakat from the business of swallow's nests due to educational factors. Perceptions of religious leaders regarding the payment of zakat on swallow's nest cultivation, namely zakat swallow is zakat that must be issued when it reaches the nisab because it is classified as agricultural zakat. The implementation of zakat for the cultivation of swallow's nests in the Benteng sub-district is carried out in accordance with the custom and knowledge of the entrepreneur so that the zakat issued is given directly to eight groups who are entitled to receive it and some are channeling it through the amil zakat agency. and an Islamic economic review regarding zakat on the cultivation of swallow's nests in the fortress village is not fully in accordance with Islamic economic principles, this is because the distribution of zakat by entrepreneurs is still given directly to mustahiq without going through the amil zakat agency, then in the utilization of zakat funds it is still consumptive because it can only meet the basic needs of mustahiq. So that zakat funds cannot be used as capital to start a business.